Joint rolling-horizon scheduling of materials processing and lot-sizing with sequence-dependent setups - de Araujo, Silvio A.; Arenales, Marcos N.; Clark, Alistair R. (Springer, 2007)
A lot sizing and scheduling problem from a foundry is considered in which key materials are produced and then transformed into many products on a single machine. A mixed integer programming (MIP) model is developed, taking into account sequence-dependent setup costs and times, and then adapted for rolling horizon use. A relax-and-fix (RF) solution heuristic is proposed and computationally tested against a high-performance MIP solver. Three variants of local search are also developed to improve the RF method and tested. Finally the solutions are compared with those currently practiced at the foundry.
Keywords: lot-sizing; scheduling; sequence-dependent setup costs and times; fix-and-relax; local search